On telemedicine and healthcare spending - Mouhcine Guettabi; Rabecca I. Arnold; Elizabeth D. Ferucci (International Journal of Circumpolar Health)
The use of telemedicine has increased substantially worldwide prompting questions about its effect on health outcomes, utilisation rates, and healthcare costs. Using de-identified data from the Alaska Tribal Health System (ATHS) and Medicaid, we evaluate how spending patterns changed for a group of telemedicine users relative to a matched sample of non-users. We find that individuals tend to incur lower healthcare spending relative to the control group after first exposure to telemedicine. Our pre- ferred estimates show a 1.14% decrease for the Medicaid sample and a 0.7% decrease in the ATHS sample.